Recent Innovations in Retinal Laser Therapy - Mi Zheng; Yannis M. Paulus (Photonics)
The early history of retinal laser therapy began with the observation of solar blindness, leading to the development of various laser technologies for treating retinal diseases. The first retinal photocoagulation machine was developed in 1956, and subsequent advancements introduced ruby and argon lasers. While conventional theories posited that retinal damage was an indispensable prerequisite for therapeutic effects, emergent insights highlight the non-damaging mechanisms, such as photostimulation- and self-repair-related mechanisms. Novel therapies, such as subthreshold micropulse laser (SMPL) and selective retina therapy (SRT), are now being employed alongside innovative delivery systems to improve treatment efficiency and safety. Clinical studies are underway to evaluate the efficacy of these therapies for conditions like diabetic retinopathy and central serous chorioretinopathy. Despite the challenges in standardization and long-term evaluation, these innovations represent significant progress towards safer and more effective laser treatment for retinal diseases.